Updating professional competencies in health informatics: A scoping review and consultation with subject matter experts - Monkman, Helen; Mir, Samiha; Borycki, Elizabeth M.; Courtney, Karen L.; Bond, Jason; Kushniruk, Andre W. (International journal of medical informatics (Shannon, Ireland), 2023)
The discipline of health informatics emerged to address the need for uniquely skilled professionals to design, develop, implement, and evaluate health information technology. Core competencies are an essential pre-requisite for establishing a professional discipline such as health informatics. In 2012, Digital Health Canada released a framework (DHC Framework) for Canadian health informatics competencies. Multiple perspectives on health informatics competencies have evolved to reflect global and unique country contexts. In this paper, we will describe a two-phase study in which we ultimately developed a new framework for health informatics competencies. In Phase 1, we conducted a scoping review of to identify health informatics competencies from research articles and grey literature from professional associations. Of 1038 articles identified in the search, ultimately 38 met our inclusion criteria and were subject to in-depth analysis. We summarized our findings from this phase into a preliminary framework of health informatics competencies and then in Phase 2, we shared these findings with subject matter experts (SMEs; N = 5) to garner their feedback. The SMEs were all instructors in health informatics in Canada and held various roles (director, professor, advisor, and co-operative education coordinator). We used their insights into the current and forecasted Canadian health informatics landscape to iteratively develop a new framework until we achieved consensus amongst the subject matter experts. In Phase 1, all competencies of the DHC Framework were supported by the literature. However, we also identified two emergent competencies: Human Factors and Data Science. In Phase 2, consultations with SMEs guided the introduction of one new competency category and seven new competencies. One competency was renamed and two were removed from the DHC Framework. Additionally, we added new terms that encompass the framework and labelled the core of the framework Health Informatics Professionalism. We found that the DHC Framework did not capture all necessary competencies required by health informatics professionals. Based on the literature and consultations with SMEs, we extended the DHC Framework to better reflect the current Canadian context and propose a new Health Informatics Core Competencies Framework. The new framework can be used to inform Canadian health informatics programs to ensure graduates are equipped for careers in health informatics. Future work includes validating the new framework with Canadian health informatics employers to assess whether this new framework adequately reflects their needs, and more detail may be required to define specific skills necessary in each competency.